1989
DOI: 10.1111/j.1464-0597.1989.tb01208.x
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation Attitudes in Plural Societies

Abstract: Dans les socittts culturellement diversifites, les individus peuvent pr6senter des attitudes relatives A leurs relations avec les autres et les groupes. Ces attitudes (dites "attitudes d'acculturation") sont libes A des prises de position sur deux problkmes gtntraux p o s h A toute p e r s o~e en acculturation: la preservation culturelle de son propre group et le contact avec les autres groupes. On dtfinit les attitudes d'assimilation, d'inttgration, de stparation et de marginalisation, puis on les mesure dans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
623
5
77

Year Published

1996
1996
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 816 publications
(717 citation statements)
references
References 12 publications
(13 reference statements)
12
623
5
77
Order By: Relevance
“…For example, Berry, Kim, Power, Young, and Bujaki (1989) developed the Acculturation Attitudes Scale (AAS). AAS requests the respondents to rate their agreement with each of the four strategies in five domains:…”
Section: Yes Nomentioning
confidence: 99%
“…For example, Berry, Kim, Power, Young, and Bujaki (1989) developed the Acculturation Attitudes Scale (AAS). AAS requests the respondents to rate their agreement with each of the four strategies in five domains:…”
Section: Yes Nomentioning
confidence: 99%
“…This particular profile involves a preference for the majority group. This profile is akin to what researchers refer to as an assimilationist approach, whereby individuals will distance themselves from their ethnic group and develop relationships with members of the majority group (Berry, Kim, Power, Young, & Bujaki, 1989). Studies have found that this latter profile is more likely to be maladaptive and lead to psychological distress among Acadians who occupy a minority status (Noël & Beaton, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Dersom et helsetilbud utformes på bakgrunn av kulturen og behovene hos majoritetsgruppen, vil tilgjengeligheten for individer fra andre grupper henge sammen med graden av integrering, assimilering og eksisterende separasjons-og marginaliseringsstrategier. Hvor mye stress eller tilpasning den enkelte vil oppleve er individuelt (Berry, 1997(Berry, /1989.…”
Section: Innledningunclassified
“…Andel legevaktkonsultasjoner ble beskrevet i prosent på bakgrunn av primaerlegekonsultasjonene som hadde foregått på legevakt. Variablene som ble identifisert gjennom analysen av intervjuene med fastleger og nøkkelinformanter ble bekreftet av litteraturen (Berry, 1989;Berry, 1992). De avhengige variabler i regresjons-analysene som ble gjort i STATA 11 var alder, kjønn, fødeland og botid i Norge.…”
Section: Kvantitativ Metodeunclassified
See 1 more Smart Citation